2012
DOI: 10.4319/lo.2012.57.4.1245
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacteria as a carbon source for zooplankton in eutrophic Lake Taihu, China, measured by 13C labeling and fatty acid biomarkers

Abstract: Using a combined stable-isotope and fatty-acid approach, we examined carbon-transfer routes from the cyanobacterium Microcystis to zooplankton in eutrophic Lake Taihu, China. Microcystis is generally considered poor food for zooplankton, and we hypothesized that most Microcystis carbon flows to zooplankton via dissolved organic matter (DOM)-bacteria and detritus-bacteria pathways rather than via direct grazing. The hypothesis was tested by analyzing 13 C isotopes at natural abundance in field samples and in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(54 citation statements)
references
References 48 publications
4
49
0
1
Order By: Relevance
“…Recently, some studies confirmed that cyanobacteria blooms and dead organisms (detritus) could be regarded as important food sources for zooplankton consumers, which eventually supported a significant share of the secondary production of lakes (Tillmanns et al, 2008). Carbon stable-isotope approach and carbon budget method have elucidated that heterotrophic bacteria were an important link between Microcystis and zooplankton (Christoffersen et al, 1990;de Kluijver et al, 2012). These microheterotrophic organisms, including flagellates and small ciliates, feed on bacterioplankton and form a 'microbial loop'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies confirmed that cyanobacteria blooms and dead organisms (detritus) could be regarded as important food sources for zooplankton consumers, which eventually supported a significant share of the secondary production of lakes (Tillmanns et al, 2008). Carbon stable-isotope approach and carbon budget method have elucidated that heterotrophic bacteria were an important link between Microcystis and zooplankton (Christoffersen et al, 1990;de Kluijver et al, 2012). These microheterotrophic organisms, including flagellates and small ciliates, feed on bacterioplankton and form a 'microbial loop'.…”
Section: Discussionmentioning
confidence: 99%
“…While considering the Microcystisdominated status, the diet of Cladocerans was modified to be more detritivorous according to the stable-isotope research in the eutrophic Lake Taihu (de Kluijver et al, 2012). The diet compositions of Zoobenthos were exclusively simplified as detritivorous.…”
Section: Diet Compositionmentioning
confidence: 99%
“…In general, phytoplankton is a preferred food source for zooplankton, but zooplankton may not be able to directly use only phytoplankton as a food source because some cyanobacteria are inedible and the elevated POM concentration likely results from the increase in input of terrestrial organic matter during the monsoon season (Lee et al 2013, De Kluijver et al 2012. Some cyanobacteria can be unsuitable as a food source for herbivorous zooplankton and inhibit not only feeding ability but also zooplankton growth (Chen et al 2005).…”
Section: Field Sampling and Analysismentioning
confidence: 99%
“…In reservoirs with large inputs of nutrients and organic matter during summer monsoon storms, zooplankton δ 13 C values are likely most closely controlled by selective zooplankton grazing in the post-monsoon season (Kankaala et al 2010, De Kluijver et al 2012. The reservoirs selected for this study commonly experience cyanobacteria blooms following the monsoon season (post-monsoon).…”
Section: Introductionmentioning
confidence: 99%
“…Although the lake is well-mixed and usually turbid due to sediment resuspension and high phytoplankton biomass, a clear water phase may be observed in spring and early summer due to low phytoplankton abundance. Water transparency decreases later in summer due to Microcystis blooms, while large zooplankton, particularly Daphnia spp., decrease in density, most likely due to increased fish predation and reduced food quality (Yang et al, 2008;Song et al, 2010;De Kluijver et al, 2012). In this study, the role of zooplankton in nutrient cycling in Lake Taihu was evaluated through estimates of P release and flux by metazoan zooplankton were estimated compared with data on P release from sediments and external P loading gleaned from the literature.…”
Section: Introductionmentioning
confidence: 99%